ANALYSIS OF THE EFFICIENCY OF THE VOICE IDENTIFICATION SYSTEM BASED ON MFCC AND GMM-SVM UNDER THE INFLUENCE OF INTERFERENCE IN THE COMMUNICATION CHANNEL - Lavrynenko, Oleksandr; Bakhtiiarov, Denys; Konakhovych, Georgiy; Kurushkin, Vitalii (Science-based technologies, 2023)
The article deals with the issue of voice identification of a person under the influence of interference in the communication channel of information and telecommunication networks. Such identification is subject to all kinds of hardware distortions and interference due to the peculiarities of equipment and devices for recording, processing and storing information, and it should also be noted that external acoustic noise inevitably superimposes on the speech signal, which can significantly distort individual informative characteristics. For this reason, identification systems that have demonstrated fairly high efficiency in laboratory conditions may show much lower reliability when analyzing speech information with external noise. Finally, in a number of tasks, identification has to be performed in very difficult conditions of overlapping voices of several speakers, in particular, with similar acoustic characteristics. It should be noted that there has been virtually no research on voice identification capabilities for this most difficult case. In view of this, the main objective of the study is to analyze the effectiveness of a voice identification system based on MFCC and GMM-SVM under the influence of interference in the communication channel of information and telecommunication networks, which will allow us to quantify the threshold values of noise power under the influence of which the identification of a person will be correct and at which it will be false. The proposed voice identification system is implemented using the following technologies: 1) selection of active speech areas with finding the values of the change in short-term energy and the number of zero crossings between adjacent frames of the speech signal; 2) adaptive wavelet filtering of the speech signal to solve the problem of noise removal, where it is necessary to conduct adaptive generation of micro-local thresholds, which will reduce the effect of additive noise on the pure form of the speech signal; 3) identification of recognition features, where mel-frequency cepstral coefficients based on two key concepts - cepstrum and mel-scale are used as informative features of speech signal recognition in automatic voice identification; 4) classification of speech signal recognition features based on mixtures of Gaussian distributions and the support vector method using the linear Campbell kernel and the principal component method with a projection on latent structures, which in total will increase the reliability of identification, which is manifested in the reduction of errors of the 1st and 2nd kind. A methodology is proposed that allows classifying speech signals with noise by mathematical modeling of distortions through the application of a resampling algorithm based on the use of a discrete Fourier transform and allowing to increase the sampling rate by a given integer or fractional number of times, where the nonlinear distortion coefficient is used as a value that quantitatively characterizes the distortion, which is introduced as the ratio of the root mean square sum of the spectral components of the output speech signal to the root mean square sum of the spectral components of the input speech signal. Mathematical modeling of speech signal distortions made it possible to quantify the magnitude of these distortions, which can be used for correct identification of a person. This shows that the proposed approach to assessing the effects of distortion can be used to analyze the reliability of voice identification methods.